Field electron emission properties of tip bended carbon nanotubes (CNTs) - Mohd Razib, Mohd Asyraf; Abdul Rahman, Dalila; Rana, Masud; Saleh, Tanveer (Persatuan Saintis Muslim Malaysia (PERINTIS), 2024)
Field emission is a process of electron emission from a conductor using a strong electric field. The search for finding the best material for field emission has led to significant improvement, especially with nanomaterials. However, no study was conducted on the resultant structure of the M2B process as the material for field emission. In this study, we reported a field electron emission from micro-patterned Vertically Aligned Carbon Nanotubes (VACNTs). VACNTs have been successfully synthesized from an atmospheric CVD system with ethylene as a carbon source. Then, the sample was patterned with a method called micro-mechanical bending (M2B). The method used a rotated tool to move in X-, Y-, Z- direction to compact and bend the VACNTs in the direction of the tool. Interestingly, it could transform the bare VANCTs from black body absorber to become reflective. The surface of the resultant structure has shown a very low surface roughness value at 15 nm with trochoidal motion mark engraved on the surface. A field electron emission study of the CNTs exhibited a turn-on value of 2.76 V mm-1, corresponding to current densities of 100 μA cm-2. Maximum current density was found to be 0.453 mA cm-2.